Rhynchospora caduciglumis a new species of Rhynchospora section Glaucae and neotypification of Rhynchospora gollmeri (Cyperaceae) - Weber, Philipy; Trevisan, Rafael (Phytotaxa, 2017)
Rhynchospora caduciglumis, a new species of Rhynchospora sect. Glaucae C.B. Clarke is described and illustrated. The new species is similar to R. polyantha Steud., but it has shorter spikelets (2.8–4.0 vs. 4.0–5.0 mm), fascicles with fewer spikelets, deciduous scales when the achenes are mature and narrower leaves (1.6–2.0 (–3) vs. 2.0–4.0 (–4.5) mm). Rhynchospora gollmeri Boeckeler is neotypified and its disjunct distribution between Venezuela and southeastern Brazil discussed.